2022
DOI: 10.3389/fimmu.2022.871780
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Whole Blood Assay and Bead-Based Cytokine Profiling Reveal Commonalities and Diversity of the Response to Bacteria and TLR Ligands in Cattle

Abstract: Recent developments in multiplex technologies enable the determination of a large nu\mber of soluble proteins such as cytokines in various biological samples. More than a one-by-one determination of the concentration of immune mediators, they permit the establishment of secretion profiles for a more accurate description of conditions related to infectious diseases or vaccination. Cytokine profiling has recently been made available for bovine species with the development of a Luminex® technology-based 15-plex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This demonstrates successful immune activation using a standardized whole-blood PAMP stimulation assay and characterizes early age immune responses in calves to bacterial and viral PAMPs. Differences in cytokine responses to multiple TLR ligands in bovine whole blood stimulation assays has been previously characterized at a protein level 23 , 41 . However, this study identified different gene expression signatures associated with bacterial and viral ligands from 77 genes involved in the bovine immune response using a standardized assay.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates successful immune activation using a standardized whole-blood PAMP stimulation assay and characterizes early age immune responses in calves to bacterial and viral PAMPs. Differences in cytokine responses to multiple TLR ligands in bovine whole blood stimulation assays has been previously characterized at a protein level 23 , 41 . However, this study identified different gene expression signatures associated with bacterial and viral ligands from 77 genes involved in the bovine immune response using a standardized assay.…”
Section: Resultsmentioning
confidence: 99%
“…Cortisol concentrations were determined by ELISA (EIA1887, DRG International, Inc., Springfield, NJ, USA). Plasma concentrations of 15 cytokines and chemokines (Interleukins 6, 17α, 1α, 1β, 1RA, 2, 8, 10, and 4, interferon γ, TNFα, as well as chemokines 2, 3, and 4) were determined at week 1 PP at the laboratory of Dr. Gilles Foucras (UMR IHAP, ENVT, Veterinary school at Toulouse, France) using a custom bovine cytokine/chemokine bead-based multiplex assay (Merck Millipore) as described 73 .…”
Section: Methodsmentioning
confidence: 99%
“…Plasma cortisol concentration was determined by enzyme assay 38 . Concentrations of pro-inflammatory cytokines were determined using a custom bovine MilliPlex xMAP cytokine assay (Merck Millipore, France) 39 . Data was recorded on a MagPix flow cytometer using Xponent software (Luminex, Austin, TX).…”
Section: Miscellaneous Clinical Signsmentioning
confidence: 99%